2004
DOI: 10.1159/000081068
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Surfactant-Damaged Skin in Humans with Creams of Different pH Values

Abstract: Skin surface has an acidic pH, whereas the body’s internal environment maintains a near-neutral pH. The physiological role of the ‘acidic mantle’ and the function of the pH gradient throughout the stratum corneum remain unexplained. The pH gradient has been suggested to activate enzymes responsible for the maintenance of the skin barrier function and to facilitate the desquamation process in the stratum corneum. The aim of the study was to investigate the influence of pH of a moisturizing cream on barrier reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
0
27
2
1
Order By: Relevance
“…This effect continued until the end of the study (day 28) and a further decrease was observed. This finding is not in contrast to an independent study by Buraczewska and Lodén [20], where they failed to prove the superiority of a cream of pH 4.0 over a cream of pH 7.5 regarding the promotion of skin barrier recovery. However, application in this study was only for a short-term period of 7 days.…”
Section: Discussioncontrasting
confidence: 99%
“…This effect continued until the end of the study (day 28) and a further decrease was observed. This finding is not in contrast to an independent study by Buraczewska and Lodén [20], where they failed to prove the superiority of a cream of pH 4.0 over a cream of pH 7.5 regarding the promotion of skin barrier recovery. However, application in this study was only for a short-term period of 7 days.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction in skin surface pH to a physiological level strengthens the SC structure and accelerates EPB repair mechanisms in the elderly, as described in mice by Choi et al [12] . Buraczewska and Lodén [60] demonstrated that treatment with an acidic emulsion (pH 4.0) compared to treatment with a pHneutral product (pH 7.5) did not result in positive effects on SC recovery in younger volunteers. In that age group (21-54 years), physiological skin surface pH levels and a sufficient skin buffering system putatively override pH modulation by acidic products.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the effect of moisturizers of pH 4 and 7.5 showed that the pH of moisturizers seems not to be of major importance for their effects on the skin barrier: no difference in the impact on skin barrier recovery or susceptibility to an irritant was found [ 50 ] . The lack of difference in effect on skin barrier recovery of the moisturizers with acidic or alkaline pH values in our study disagrees with a previous study in mice, where barrier recovery was delayed after exposure to slightly alkaline pH [ 51 ] .…”
Section: Phmentioning
confidence: 99%
“…In the present investigation, after long-term treatment, moisturizers were examined for their effect on the skin barrier with regard to such factors as pH, lipid type, the presence of a humectant, as well as complexity of the product [27][28][29]50 ] . Moisturizers are able to modify the skin barrier function, detected as changes in TEWL, skin capacitance, and susceptibility to an irritant, and also to change the mRNA expression of certain genes involved in the assembly, differentiation, and desquamation of the stratum corneum, as well as lipid metabolism.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%